Visualization Research at the Software Engineering and Information Systems Laboratory (SEIS) - Silva, Celmar Guimarães da (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2021.20047, 2021)
This paper summarizes twelve years of visualization research at the Software Engineering and Information Systems Laboratory (SEIS), located at the University of Campinas. This research comprises theoretical and applied research in visualization and embraces themes such as the development of matrix reordering algorithms, the creation of heuristics for visualization, and the application of visualization techniques to areas such as oil engineering and educational data mining.